User accessibility to refractive error correction services in selected Zambian hospitals - Kapatamoyo, Esnart (Division of General Surgery, 2022)
Background: Uncorrected Refractive Errors (UREs) are the most common cause of vision loss globally. The burden is particularly worse in low- and middle-income countries like Zambia, where access to Refractive Error Correction Services (RECS) is limited. This study aimed to assess the user's accessibility to RECS in selected Zambian Hospitals. Methods: Twenty (20) public health facilities offering RECS were conveniently selected using a crosssectional design. These represented 20 districts in eight provinces of Zambia. A questionnaire-based on access to health care services framework was administered. The framework assessed service accessibility in terms of availability, geographical accessibility, and affordability. Facility managers completed and submitted the questionnaire via email. Results: Completed questionnaires were received from 20 facilities. Nineteen facilities were located in rural areas whilst one facility was located in an urban area. Most facilities (84%) had the Ministry of Health recommended equipment, though essential equipment such as tonometers were lacking in most facilities (70%). Fifteen facilities (75%) reported having Optometry Technologists as the main staff offering services. Only two facilities (10%) had an Ophthalmologist each and no facility had an Optometrist. School-based programmes were not carried out in all facilities. Only one (5%) facility was able to dispense spectacles soon after refraction as it had a spectacle manufacturing workshop. For some facilities (60%), a poor road network posed a challenge to geographical accessibility. Insufficient funding limited access to RECSs. Facility representative stated that not all patients could meet the cost of services in all the facilities. Conclusion: Access to refractive error correction services in the 20 facilities was limited due to a combination of eye health programme deficiencies and general challenges typical in low- and middle-income countries. Funding, human resources and equipment were insufficient. Inadequate road network and infrastructure undermined service delivery. The accessibility shortcomings identified should be used to improve user accessibility of refractive services.